Pluralizm w mediach a wolność wyboru jako fundament liberalnej demokracji - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
Modern member of the audience in Poland and elsewhere is not a subject of ethics thus he/she does not have a free choice in the philosophical (exclusively liberal and democratic) sense. He/she is surrounded by information smog as nearly identical news is provided by different sources. The journalists the audience trusts first select the important pieces of news before publishing them; secondly they process and comment them thus providing the audience with the description of the facts as well as with its interpretation and assessment. The journalists are significantly dependent on the owner who tends to treat his/her newspaper or station as a profit-oriented enterprise. By this token the owner is directly dependent on the advertisers, who need to be attracted to the same extent as the audience does. As a result, the actual freedom of choice is purely deceptive, which is not to mean it is unattainable. An individual may try to take advantage of it, yet the ultimate result depends on him/herself.